Correlation between Squamous Suture and Sylvian Fissure: Osirix DICOM Viewer Study - Rahmah, Nunung Nur (Public Library of Science, 2011)
BACKGROUND: Sylvian fissure (SF) is an important corridor in neurosurgery, and the end of sylvian fissure (eSF) represents the optimal target area to expose suitable recipient artery in STA-MCA bypass. Unfortunately little have been addressed concerning its relationship with external cranial surface. OBJECTIVE: Correlation between Squamous Suture (SS) and SF was investigated. METHODS: 50-adult 3D-CTA images were studied using OSIRIX DICOM viewer. The measurement points were determined from external auditory meatus 0, 1, 1.5, 2, 2.5, 3, 3.5 and 4-cm anteriorly, perpendicular from orbitomeatal (OM) line. The distance of SF was compared with the one of SS. RESULTS: SSs were all located below SF at 0 cm. At a distance of 0 to 1.5 cm, SSs were located above SF, then started to merge and went side by side from 2 cm anteriorly. Anterior sylvian point, the most anterior part of SF, was found at 4 cm from OM line. Inferior Rolandic point, which corresponds to the central sulcus inferior extent, was found to be at 2 cm from OM line. The eSF was identified at 0 cm anteriorly from OM, and perpendicularly 1.5 cm above SS. 50% patients had Chater's point (CP) above eSF. Average value for CP was 0.01 below eSF, giving a significantly closer value compared to the one of SS (p<0.01). However, SS showed consistent value of 1.5 below SF. Furthermore, SS is a bony landmark, which has no shifting effect during surgery, therefore drawing a 1.5-cm line upward from SS could lead to exact location of eSF. CONCLUSION: The course of SF and its correlation to SS have been identified, and this is also the first study to investigate the relationship of SS and eSF using OSIRIX DICOM viewer. SS is also comparable to CP, therefore it is usable for a simple landmark of eSF.